The Sixth Form at ST CLARE'S - Blyton, Enid; Cox, Pamela (London, UK Hodder and Stoughton)
The O'Sullivan twins are sad it's their last year at St Clare's, but there's no time to be downcast as they are head girls! They're kept busy by two cheeky first formers, sulky new girl Morag who's only happy when she can escape to the local riding stable and cruel Priscilla, a girl held back in sixth form. It's the twins last year and it certainly won't be dull!
Keywords: English-Fiction